Computer Vision Syndrome pada Dosen Tahap Akademik Fakultas Kedokteran Universitas Islam Bandung selama Pandemi COVID-19 - Farah Talitha Nawiryasa; Eva Rianti Indrasari; Herry Garna (UNISBA Press, 2022)
Abstract. Computer vision syndrome (CVS) is a group of eye and vision-related symptoms that arise due touse of computers or gadgets prolonged. Risk factors for CVS include individual, environmental, and computer factors. The use of gadgets is increasing during the COVID-19 pandemic because the government urges the public including teachers such as lecturers to work from home. This study aims to determine the incidence of CVS in lecturer at the academic stage of FK Unisba during the COVID-19 pandemic starting from February–December 2021. This type of research is quantitative with analytic observational method and cross sectional design. The instrument used is a questionnaire. In this study, data were obtained as many as 60 lecturers of the academic stage of FK Unisba with total sampling technique. The data analysis used was univariate and chi square test for bivariate analysis. The results showed that the most complained symptoms were tired eyes from asthenopia symptoms (44%), watery eyes and itchy eyes from ocular surface symptoms respectively 31%, difficulty focusing vision and increased sensitivity to light from visual symptoms respectively 24%, and shoulder pain from extraocular symptoms (40%). In conclusion, most of the lecturers at the academic stage of FK Unisba experienced CVS. The results of the analysis did not show a relationship between risk factors and the incidence of CVS (p>0.05). It is recommended that there be preventive prevention against CVS complaints. Abstrak. Computer vision syndrome (CVS) merupakan sekumpulan gejala terkait mata dan penglihatan yang muncul akibat penggunaan komputer atau gadget dalam waktu lama. Faktor risiko CVS di antaranya faktor individu, lingkungan, dan komputer. Penggunaan gadget semakin meningkat di masa pandemi COVID-19 karena pemerintah menghimbau masyarakat termasuk pengajar seperti dosen melakukan work from home. Penelitian ini bertujuan menganalisis kejadian CVS pada dosen tahap akademik FK Unisba selama pandemi COVID-19 dimulai dari Februari–Desember 2021. Jenis penelitian ini adalah kuantitatif dengan metode observasional analitik dan desain cross sectional. Instrumen yang digunakan berupa kuesioner. Pada penelitian ini didapatkan data sebanyak 60 dosen tahap akademik FK Unisba dengan teknik total sampling. Analisis data yang digunakan adalah univariat dan uji chi square untuk analisis bivariat. Hasil penelitian menunjukkan bahwa gejala yang paling banyak dikeluhkan adalah mata lelah dari gejala astenopia (44%), mata berair dan mata gatal dari gejala permukaan okular masing-masing 31%, sulit memfokuskan penglihatan dan merasa silau saat melihat cahaya terang dari gejala visual masing-masing 24%, dan nyeri bahu dari gejala ekstraokular (40%). Simpulan, sebagian besar dosen tahap akademik FK Unisba mengalami CVS. Hasil analisis menunjukkan tidak ada hubungan antara faktor risiko dan kejadian CVS (p>0,05). Disarankan pencegahan preventif terhadap keluhan CVS.